2018
DOI: 10.1002/star.201700269
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Carbohydrate Digestibility of North Indian Parotta Using Protein and Dietary Fiber Based Functional Ingredients

Abstract: Diet is the cornerstone in the management of hyperglycemia. Indian diets are predominantly cereal based providing a higher proportion of carbohydrate. Hence whole wheat flour (staple cereal) is substituted with a blend of 20-30% of chickpea flour, psyllium husk, fenugreek seed powder (CPF) for increasing the protein and dietary fiber contents. The effects of CPF on the rheological characteristics of whole wheat flour; physico-chemical, sensory characteristics, and carbohydrate digestive profile of north Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…An increase in peak viscosity can be attributed to the addition of fiber-rich fractions, i.e., psyllium husk and dried spinach. This result is consistent with the study done by Ray et al [31] They reported that a higher water holding capacity of fiber results in higher peak viscosity of the mixture. Also, an increase in peak viscosity can be attributed to the addition of protein-rich fractions like SPI and pulses in the nutrientenriched khakhra flour.…”
Section: Pasting Behaviorsupporting
confidence: 93%
“…An increase in peak viscosity can be attributed to the addition of fiber-rich fractions, i.e., psyllium husk and dried spinach. This result is consistent with the study done by Ray et al [31] They reported that a higher water holding capacity of fiber results in higher peak viscosity of the mixture. Also, an increase in peak viscosity can be attributed to the addition of protein-rich fractions like SPI and pulses in the nutrientenriched khakhra flour.…”
Section: Pasting Behaviorsupporting
confidence: 93%
“…Otra oportunidad de investigación está relacionada al porcentaje correcto de psyllium que es necesario para lograr una reducción efectiva del índice glucémico de los panes. Ray et al (2018) reemplazó harina de trigo del pan parotta (pan típico del Sur de India), por una combinación de psyllium (7,5% del peso total de la harina), harina de garbanzos y semilla de fenogreco ("fenugreek") en polvo. Ellos demostraron que con el 25% de sustitución se obtiene un incremento del almidón de lenta digestión y del almidón resistente y, en consecuencia, reducción significativa del almidón de rápida digestión.…”
Section: Aplicación Del Psyllium En Productos De Panaderíaunclassified
“…Nowadays, psyllium is the worlds' fourth most used hydrocolloid after hydroxypropyl methylcellulose (HPMC), xanthan gum and guar gum, in formulations of this type of bread (Román, Belorio, & Gómez, 2019). It has also been proposed for use in wheat bread elaborations to produce softer bread with more moisture and less staling (Czuchajowska, Paszczynska, & Pomeranz, 1992;Pejcz et al, 2018) or to slow the digestion of these types of bread (Ray et al, 2018). When elaborating bakery products using new ingredients, they must interact with starch.…”
Section: Introductionmentioning
confidence: 99%